Voltaire historian. About the Histoire de Charles XII - Ratto, Adrián (ARFIL y UNL, 2019)
The Histoire de Charles XII, roi de Suède (1731) is a work often undervalued by specialists of  Voltaire’s historical and historiographic works, insofar they see in it a minor work, which would be closer to the Henriade, the epic poem that he published in 1728 in honor of Henry IV, than to his great historical works, the Siècle of Louis XIV (1751) and Essai sur les mœurs et l’esprit des nations (1756) . The aim of this paper is to show that the Histoire of Charles XII anticipates, in spite of being one of the Voltaire’s earliest historical writings, the method that he would use from the 40’s in his major works. In addition, the text highlights the existence of a certain distance between the program the philosopher intended to implement on the writing and its material form. On the other hand, the article sheds some light on the role of the “great men” in Voltaire’s philosophy of history.